Supercritical carbon dioxide extraction and studies of mango seed kernel for cocoa butter analogy fats = Extracción mediante dióxido de carbono supercrítico y estudios del núcleo de la semilla de mango para obtener grasas análogas a la mantequilla de cacao - Jahurul, Md. Haque Akanda; Sarker, Md. Zaidul Islam; Nik Abd. Rahman, Nik Norulaini; Ferdosh, Sahena; Md. Jaffri, Juliana; Kadir, Mohd Omar (Taylor & Francis Online, 2014)
Supercritical carbon dioxide (SC-CO2) was introduced for obtaining premium grade cocoa butter quality fat from the waste of mango seed kernel (MSK), where the Soxhlet method was also used for the comparison. Six different varieties of MSK were selected to be extracted using SC-CO2 at pressures of 35 and 42.2 MPa, temperatures of 60°C and 72°C, and constant CO2 flow rate at 3.4 ml/min. The total fat contents of MSK varieties ranged from 64 to 135 g/kg at SC-CO2 extraction and from 76 to 137 g/kg at Soxhlet extraction methods. The fatty acid constituents of fat yield of all varieties extracted using SC-CO2 ranged from 6.9% to10.9% palmitic acid, 32.8% to 47.6% stearic acid, 37% to 47.3% oleic acid, and 3.7% to 6.9% linoleic acid. However, the physicochemical properties and fatty acid constituents of SC-CO2 extracted MSK fats were found to be comparable to that of commercial cocoa butter.